Small Interfering RNA for Gliomas Treatment: Overcoming Hurdles in Delivery - Teng, Xin-Qi; Qu, Jian; Li, Guo-Hua; Zhuang, Hai-Hui; Qu, Qiang (Frontiers in Cell and Developmental Biology, 2022)
Gliomas are central nervous system tumors originating from glial cells, whose incidence and mortality rise in coming years. The current treatment of gliomas is surgery combined with chemotherapy or radiotherapy. However, developing therapeutic resistance is one of the significant challenges. Recent research suggested that small interfering RNA (siRNA) has excellent potential as a therapeutic to silence genes that are significantly involved in the manipulation of gliomas’ malignant phenotypes, including proliferation, invasion, metastasis, therapy resistance, and immune escape. However, it is challenging to deliver the naked siRNA to the action site in the cells of target tissues. Therefore, it is urgent to develop delivery strategies to transport siRNA to achieve the optimal silencing effect of the target gene. However, there is no systematic discussion about siRNAs’ clinical potential and delivery strategies in gliomas. This review mainly discusses siRNAs’ delivery strategies, especially nanotechnology-based delivery systems, as a potential glioma therapy. Moreover, we envisage the future orientation and challenges in translating these findings into clinical applications.